2021
DOI: 10.1016/j.hemonc.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Splenic marginal zone lymphoma associated with hepatitis B virus infection, remission after viral treatment, and splenectomy

Abstract: We report the case of a patient diagnosed with a splenic marginal zone lymphoma with a simultaneous finding of hepatitis B virus infection, who responded to antiviral treatment and splenectomy. We highlighted this association described in the literature and its possible causal role, as well as the available therapeutic choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In certain non-CNS extranodal tissue sites, the development of MZBL has been described in association with specific chronic infectious and autoimmune processes, such as within gastrointestinal mucosa colonized by H. pylori and within lacrimal glands in Sjögren syndrome [3,5]. A small number of cases of patients with both HBV and MZBL have been reported in the literature, consistent with our second reported patient who presented with multifocal lesions and a long-standing history of untreated HBV [6]. This raises consideration for potential mechanisms behind the pathogenesis of CNS MZBL in our second patient, possibly arising either secondarily to direct chronic antigenic stimulation of the dura or as metastasis from an HBV-associated primary extracranial MZBL that went undetected on PET-CT.…”
Section: Discussion/conclusionsupporting
confidence: 88%
“…In certain non-CNS extranodal tissue sites, the development of MZBL has been described in association with specific chronic infectious and autoimmune processes, such as within gastrointestinal mucosa colonized by H. pylori and within lacrimal glands in Sjögren syndrome [3,5]. A small number of cases of patients with both HBV and MZBL have been reported in the literature, consistent with our second reported patient who presented with multifocal lesions and a long-standing history of untreated HBV [6]. This raises consideration for potential mechanisms behind the pathogenesis of CNS MZBL in our second patient, possibly arising either secondarily to direct chronic antigenic stimulation of the dura or as metastasis from an HBV-associated primary extracranial MZBL that went undetected on PET-CT.…”
Section: Discussion/conclusionsupporting
confidence: 88%
“…Recently, some studies have shown coexistence between chronic hepatitis B virus infection and splenic lymphomas, particularly SMZL, suggesting a new etiological association for this neoplasm. Similar to that observed in HCV positive cases, treatment for HBV with antiviral agents is capable of inducing neoplasm remission [ 23 26 ].…”
Section: Discussionmentioning
confidence: 72%
“…The possible mechanisms behind the pathogenesis of CNS MZBL could be represented by a localization of an undetected primary extracranial MZBL or a chronic in ammation. This last condition could derive from a direct chronic antigenic stimulation of the dura, for example for a long-standing history of untreated HBV [12,13] or HCV [14]. One patient with CNS MZBL had a long history of white matter disease with some features of multiple sclerosis [5] and another patient was suffering from a Chlamydia psittaci infection [15].…”
Section: Case and Literature Discussionmentioning
confidence: 99%